2019
DOI: 10.2174/2210315509666190117151542
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Cardamonin and Pinostrobin Chalcone from the Rhizomes of Boesenbergia rotunda (L.) Mansf. and their Cytotoxic Effects on H-29 and MDA-MB-231 Cancer Cell Lines

Abstract: <P>Background: Breast cancer and human colon cancer are the most common types of cancer in females and males, respectively. Breast cancer is the most common type of cancer after lung and colon cancers. Natural products are an important source for drug discovery. Boesenbergia rotunda (L.) Mansf. is commonly known as finger root, belonging to the Zingiberaceae family. </P><P> Objective: The aim of this study to isolate some natural compounds from the rhizomes of B. rotunda (L.) Mansf., and to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…For example, B. pandurate-derived panduratin A showed an IC 50 value of 3.75 µg/mL against non-TNBC cells (MCF-7) through a 72 h MTT assay [19]. B. rotunda-derived cardamonin showed IC 50 values of 5.62 and 26.7 µg/mL against TNBC cells (MDA-MB-231) [26] and nasopharyngeal (HK1) [21] cancer cells, whereas the IC 50 values of normal nasopharyngeal epithelial cells (NP69) were >200 µg/mL. This suggests cardamonin exhibits anticancer effects without severe side effects in normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, B. pandurate-derived panduratin A showed an IC 50 value of 3.75 µg/mL against non-TNBC cells (MCF-7) through a 72 h MTT assay [19]. B. rotunda-derived cardamonin showed IC 50 values of 5.62 and 26.7 µg/mL against TNBC cells (MDA-MB-231) [26] and nasopharyngeal (HK1) [21] cancer cells, whereas the IC 50 values of normal nasopharyngeal epithelial cells (NP69) were >200 µg/mL. This suggests cardamonin exhibits anticancer effects without severe side effects in normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pinostrobin demonstrated a strong antitumor activity on mammary carcinoma cells, which was partially explained by topoisomerase inhibition [82][83][84]. This enzyme is responsible for DNA strand break repair, allowing the broken strand to rotate on the intact one and reducing the torsional tension of the molecule during the process [85].…”
Section: Antitumor Propertiesmentioning
confidence: 99%
“… 27 Numerous biological potentials exhibited by this flavanone including antioxidants, 28 anti-inflammatory, 29 augmentations of inflammatory cytokines (interleukin-1β, tumour necrosis factor (TNF)-α) 30 and anti-ulcerogenic actions. 26 Moreover, in vitro , studies revealed outstanding inhibitory efficacy of PN against the growth of breast cancer, 31 cervical, 32 lung cancers, 33 HL-60 and K562 leukaemia cells. 34 Moreover, PN also exhibited significant free radical quenching and anti-inflammation actions in silver nanoparticle-treated fibroblasts.…”
Section: Introductionmentioning
confidence: 99%